The Daily Linguistic Practice Interview: A new instrument to assess language use and experience in minority language children and their effect on reading skills - Desiré Carioti; Silvia Stefanelli; Ambra Giorgi; Marta Franca Masia; Giulia Del Pivo; Milena Del Monte; Simona Travellini; Antonella Marcelli; Maria Teresa Guasti; Mirta Vernice; Manuela Berlingeri (Ampersand, 2024)
The increasing number of primary students with varying degrees of exposure to a family minority language requires a reflection on whether specific aspects of their daily language experience influence their learning. Indeed, Minority Language Children (MLC) often report difficulties in reading that must be better investigated to exclude neurodevelopmental conditions such as developmental dyslexia.To this aim, we developed a new instrument, the Daily Linguistic Practice Interview. It allows for collecting information about the linguistic practice and use in the family (Scale A) and extra-family context (Scale B), and about the child's linguistic preferences and habits (Scale C). The Interview further provides analogic quantitative measures of minority language active speaking with mother, father, and passive listening, in the form of clocks to paint.The relationship between these linguistic aspects and reading skills was investigated on 79 MLC aged 8 to 11 y.o.through a correlational approach and regression models. Our results show that family and extra-family language use influence accurate lexical recognition, moreover a “mother effect” broadly affects reading skills in the majority language.Our findings suggest that MLC deserve a more careful evaluation of learning disorders with ad hoc standardized tests, that incorporates information about the family language exposure.